Scientific Speaker Apprenticeship Program - Andrew Phillips; David Diller; Gus Garmel (Association of American Medical Colleges, 2015)
Abstract This is a short, focused curriculum designed to introduce young scientists to the art of lecturing. It was tested with medical residents in emergency medicine, but the principles apply to any scientific presentation. The curriculum includes brief background reading, a video lecture about giving presentations hosted by a well-respected emergency medicine lecturer, and instructions for mentorship by other faculty, all in preparation for the trainee to give a lecture at a conference with the faculty mentor. Feedback from the faculty mentors, resident participants, and resident audience members was positive. This curriculum provides a structured way to permit a trainee to succeed early on the lecture circuit in a safe yet live environment. All nine faculty mentors reported in a post-implementation survey that they would recommend this program to their residents and faculty colleagues. The resident participants also unanimously reported in a separate survey that they would recommend this program to their trainee colleagues. They further reported that both the preparatory lecture on lecturing and the mentorship generally aided both content and delivery of their lectures. A focus group with the audience found positive feedback as well. The group's consensus was that the residents brought a helpful perspective to the lectures.